Nurturing students’ spiritual development in secular contexts: a case study of Evangelical theological education in Australia - P.E. Momoh; M. Naidoo (Acta Theologica)
The awareness of secularisation may not have served as a focus for curricula development in theological education, yet it critically shapes the entire educational process influencing values and practices. Australian theological colleges need to be aware of, and alert to their secular, westernised culture that places a high premium on individual rights, personal liberty, and freedom. This article reports on an Australian study discussing the nature of secularised contexts and the relevance of evangelical theological education to these contexts, especially the role of spiritual formation as a key component to better equip theological students to deal with their secular context. The article argues for stronger awareness of, and preparedness for robust engagement with secularised contexts. It highlights the importance of engaging the influence of secularisation values in theological education.